Dissecting the signal transduction pathways triggered by galectin-glycan interactions in physiological and pathological settings - Laderach, Diego Jose (2010)
Galectins are a family of evolutionarily conserved animal lectins with pleiotropic functions and widespread distribution. Fifteen members have been identified in a wide variety of cells and tissues. Through recognition of cell surface glycoproteins and glycolipids, these endogenous lectins can trigger a cascade of intracellular signaling pathways capable of modulating cell differentiation, proliferation, survival, and migration. These cellular events are critical in a variety of biological processes including embryogenesis, angiogenesis, neurogenesis, and immunity and are substantially altered during tumorigenesis, neurodegeneration, and inflammation. In addition, galectins can modulate intracellular functions and this effect involves direct interactions with distinct signaling pathways. In this review, we discuss current knowledge on the intracellular signaling pathways triggered by this multifunctional family of β-galactoside-binding proteins in selected physiological and pathological settings. Understanding the “galectin signalosome” will be essential to delineate rational therapeutic strategies based on the specific control of galectin expression and function.